Multipropriedade: um instrumento de eficácia da função social e da função econômica da propriedade imóvel - Rocha, Ana Maria Muniz dos Santos (2022)
In summary, the research looks at the issue of fundamental rights to property from the perspective of co-ownership in timeshares. All research is carried out with the aim of verifying the hypothesis that timeshares are an effective instrument for the effective social and economic functioning of property. The problem that originates from such a hypothesis is the existence of vacant or occasional-use properties which are therefore underused and result in the property being unable to fulfil several of its functions. As for the methodology, the research was carried out using the deductive method with the aid of the logical-semantic constructivism method. In addition, the documentary and bibliographic technique was used. The first chapter addresses the broad issue of fundamental rights in property and considers what the proper social and economic function of property is. The second chapter looks at timeshares and the nuances brought by Law nº 13.777/2018 and then looks at the relationship between co ownership in timeshares (as a form of exercising the fundamental right to property) and how this legal construction is able to make more effective the social and economic function of real estate. The research concludes that as a result of reducing the time in which a property remains idle, that timeshare property enables the proper social and economic functioning of the property.